2019
DOI: 10.4102/sajp.v75i1.471
|View full text |Cite
|
Sign up to set email alerts
|

Community-based primary healthcare training for physiotherapy: Students’ perceptions of a learning platform

Abstract: Background South Africa is faced with an overburdened public healthcare system and physiotherapists need to be equipped to address these challenges. Community-based primary healthcare clinical training (CBPHCT) offers physiotherapy students with learning opportunities to develop core competencies in order to address the needs of a disparate healthcare system. Objectives To explore the experiences of physiotherapy students participating in a CBPHCT platform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 17 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Even if technological and set up investments for online teaching are required, studies have shown that switching to online teaching can reduce costs for students [ 26 ] which in turn can increase students numbers, especially in those countries where loans for tuitions are a major barrier to university attendance [ 27 , 28 ]. However, building up a digital educational system may increase disparities towards people living in remote and rural regions, poorer social classes, and families experiencing financial difficulties due to COVID-19 induced economic crisis [ 26 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if technological and set up investments for online teaching are required, studies have shown that switching to online teaching can reduce costs for students [ 26 ] which in turn can increase students numbers, especially in those countries where loans for tuitions are a major barrier to university attendance [ 27 , 28 ]. However, building up a digital educational system may increase disparities towards people living in remote and rural regions, poorer social classes, and families experiencing financial difficulties due to COVID-19 induced economic crisis [ 26 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, preventive measures cannot be taken if there is no awareness, especially in certain social groups responsible for health, about the harmfulness of certain factors (risk factors), as well as no ability to distinguish them in society. This knowledge which is transferred to patients should result in their efforts to eliminate danger or at least limit its negative impact on their health [14,20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate substantive preparation of medical professionals (physicians, physiotherapists, nurses and midwives) to their profession, which commenced during their studies and continued throughout their postgraduate education, will signi cantly affect the health of those people who come to clinics and hospitals. Education and knowledge about health promoting behaviour should be expanded with regard to the existing dangers of losing health, aspects affecting our health, and factors which contribute to diseases [2,3,6,20,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of adequate digital resources (e.g. bandwidth connectivity, availability of hardware, and internet) constitutes a barrier to learning for those students living in rural regions and in developing countries [50]. There is a chance that some students who have not enough digital resources at home will not be able to cope with the contingent technology demand, affecting their learning outcomes [2,49].…”
Section: Unresolved Dilemmasmentioning
confidence: 99%